The Effects of Self-Learning Kits on the Academic Performance of Selected Grade 4 Learners in ESP (Edukasyon Sa Pagpapakatao) - Jesus, Dennis A. De; Austria, Windel C. (International Journal of Atharva, 2025)
This study investigated the effects of Self-Learning Kits (SLKs) on the academic performance of selected Grade 4 learners in Edukasyon sa Pagpapakatao (ESP) at Sta. Maria Elementary School. A quasi-experimental design was employed using a pre-test and post-test to determine performance differences before and after the intervention. The study revealed a statistically significant improvement in learners’ academic performance after the use of SLKs. The SLKs, developed based on localized and learner-centered strategies, proved to be a viable instructional tool for fostering independent learning and deeper comprehension of core values in ESP. Findings emphasize the need for inclusive, contextualized educational tools that respond to learners’ cognitive and socio-emotional needs. These results contribute to a growing body of literature advocating the integration of supplementary materials in values education and serve as a guide for educators, administrators, and policymakers.